Nontronite-bearing tubular hydrothermal deposits from a Galapagos seamount. (April 2018) - Lubetkin, Megan; Carey, Steven; Kelley, Katherine A.; Robert, Geneviève; Cornell, Winton; Raineault, Nicole; Balcanoff, Jacob; Ballard, Robert D.; Salinas-de-León, Pelayo
Abstract: A telepresence-enabled cruise using remotely operated vehicle (ROV) exploration discovered an unusual tubular deposit of Fe-rich hydrothermal nontronite on a young seamount, Mashi, of the Wolf-Darwin lineament in the Galápagos Islands. X-ray diffraction, ICP-MS, ICP-AES, and SEM-EDS analyses show that this deposit is chemically and mineralogically similar to other deep-sea hydrothermal nontronites, indicating a likely formation temperature of about 30° to 50 °C by diffuse hydrothermal activity. These deposits contain mixtures of Fe-rich, Al-poor nontronite and poorly crystalline Fe-Si-oxyhydroxides with bulk compositions of 38–51 wt% SiO2 and 40–50 wt% Fe2 O3 *. The presence of filamentous and spherical structures in the samples suggests that mineral deposition was in part facilitated by chemosynthetic microbes. Although hydrothermal nontronite has been sampled at a number of seafloor sites by coring and dredging, this is the first in situ documentation of its unusual sinuous, tubular structure, on the seafloor. Quantitative image-analysis of ROV imagery indicates that hydrothermal fluid pathways, developed through an underlying pillow lava sequence, likely control the distinctive sinuous morphology.